Milling of Heat-Treated Beech Wood (Fagus sylvatica L.) and Analysis of Surface Quality - Mihai Ispas; Lidia Gurau; Mihaela Campean; Murat Hacibektasoglu; Sergiu Racasan (BioResources, 2016)
Several previous studies have investigated the effects of heat treatment on the chemical composition, along with the physical and mechanical properties, of wood from various species. However, the effects of these property changes upon the machining properties and surface quality of machined wood have been studied much less. The main goal of this work was to investigate the comparative cutting power consumption during milling and the resulting surface roughness of heat-treated and untreated beech wood (Fagus sylvatica L.). Several cutting regimes were tested by combining different values of rotation speed, feed speed, and cutting depth. The cutting power and the processing roughness were assessed and compared. The results clearly showed that the cutting power involved in the milling of heat-treated beech wood was up to 50% lower than that of untreated wood, but the processing roughness was slightly higher.
Keywords: Heat-treated beech wood; Machinability; Cutting power; Surface quality; Processing roughness; Waviness